The Fetishization Effect: The Manipulation Power of the Machete in the Rwandan Genocide. (25th February 2018) - Fallon, Breann
Abstract : The perpetrators of the Rwandan Genocide were the most efficient killers of the twentieth century, with 8000 victims per day at a modest count. Tribal tensions, Belgian Colonization, and the Church are frequently highlighted as foundational to the slaughter in 1994, but this paper suggests an additional, overlooked propellant behind the actions of Hutu perpetrators - the machete. Via an investigation of primary perpetrator (Hatzfeld 2003) and victim accounts (Gourevitch 1998), this paper presents a new spiritual, psychological, and social paradigm around the fetishization (Ellen 1988) of the machete in the Rwandan Genocide - 'The Fetishization Effect.' This paradigm occurs in three stages - unification, operation and fetishization - for the machete comes to unify community, create a new 'imagining' of reality (Anderson 1991, 7) and is thus unconsciously enchanted with a divine essence. When fully fetishized, the inspirited machete was able manipulate perpetrator psyche, propel violent actions, justify final blows, and absolve the perpetrator of consequence. This weapon was no inanimate object, but rather a manipulative 'machine of power' (Ellen 1988, 228) complicit in the murder of the Tutsi population. As such, this paper will delineate this paradigm, explicating the machete's role in the creation of the 'true Rwandan' community and their new reality, displaying the subsequent inspiriting of the machete by this group, through which it came to influence, control, and substantiate their actions.